The Development of Story Methods in Learning Islamic Education Based on NLP (Neuro-Linguistic Programming) in Elementary Schools - Amar, Muh Zulfikar (Pedagogik Journal of Islamic Elementary School, 2020)
The purpose of this study was to determine the results of the analysis of the need for PAI learning methods in grade V students at SDN 50 Bulu 'datu Palopo, to find out the validity of developing NLP-based story methods in PAI learning and assessing the effectiveness of NLP-based story methods in PAI learning. This research method is the Research & Development (R&D) method. The development model used is ADDIE which consists of five stages, namely: Analysis, design, development, implementation, and evaluation. Research subjects in class V SDN 50 Bulu 'Datu Palopo amounted to 15 students. Data collection techniques are questionnaires, documentation, observation, interview, and validation. Data analysis techniques to test their validity using the Aiken's formula and student questionnaire responses using descriptive statistical analysis. The results of this study indicate that in learning PAI especially the material of the stories of the Prophet and the Apostle needed the development of learning methods namely the NLP-based story method. The NLP-based story method developed was declared valid by three validators with a recapitulation of 0.67. Learning methods have been effective in using students' questionnaire responses.